2013
DOI: 10.1111/echo.12121
|View full text |Cite
|
Sign up to set email alerts
|

Right Atrial Indexed Volume in Healthy Adult Population: Reference Values for Two‐Dimensional and Three‐Dimensional Echocardiographic Measurements

Abstract: This is the first study that reports the reference indexed right atrial volume values by means of 2D-echo and 3D-echo in healthy population. 3D-WMT is a feasible and reproducible method to determine right atrial volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 20 publications
0
10
0
3
Order By: Relevance
“…38 They were followed by other authors also using 3DE imaging. [39][40][41] All these studies reported a significant underestimation of 2DEderived RA volume in comparison with 3DE. Figure 2 shows the 3DE evaluation of RA phasic function, whereas Table 1 shows reference 2DE and 3DE values.…”
Section: Right Atrial Size and Volumementioning
confidence: 97%
See 2 more Smart Citations
“…38 They were followed by other authors also using 3DE imaging. [39][40][41] All these studies reported a significant underestimation of 2DEderived RA volume in comparison with 3DE. Figure 2 shows the 3DE evaluation of RA phasic function, whereas Table 1 shows reference 2DE and 3DE values.…”
Section: Right Atrial Size and Volumementioning
confidence: 97%
“…Aune et al were the first who presented normal ranges of 3DE‐derived RA volumes in 166 healthy subjects . They were followed by other authors also using 3DE imaging . All these studies reported a significant underestimation of 2DE‐derived RA volume in comparison with 3DE.…”
Section: Right Atrial Size and Volumementioning
confidence: 98%
See 1 more Smart Citation
“…Measuring RA size provides prognostic information for several conditions, such as arrhythmias, pulmonary hypertension, valvular lesions, and congenital heart disease. 15,16 RA size is recommended to be reported as volume acquired from apical four-chamber view either with area-length or Simpson disk summation method. 6,17 Normal ranges presented in the guideline are 25 AE 7 mL/m 2 in men and 21 AE 6 mL/m 2 in women.…”
Section: Right Atriummentioning
confidence: 99%
“…The Young Finns study is an ongoing longitudinal population-based study into the evolution of cardiovascular risk factors from childhood to adulthood. 7,8 The participants were 3,6,9,12,15, and 18 years of age at the beginning of the study in 1980. Echocardiography was performed in 2011 for 1,994 participants (914 men and 1080 women, mean age 41.9 AE 5.0 years, range 34-49 years).…”
mentioning
confidence: 99%